Ion induced fragmentation of diatomic molecular clusters. Issue 15 (January 2020) - Méry, A; Agnihotri, A N; Douady, J; Fléchard, X; Gervais, B; Guillous, S; Iskandar, W; Jacquet, E; Kumar, V; Matsumoto, J; Rangama, J; Ropars, F; et al.
Synopsis: Weakly bound atomic or molecular clusters are of growing interest in the fields of atmospheric science, hadron-therapy or astrophysics. We will present our recent experimental results on the fragmentation of diatomic molecular dimers after irradiation by highly charged ions. For (N2 )2 dimers, the measured KER spectrum is very similar to the one of the N2 monomers but is globally shifted towards higher energies. Moreover, sequential dissociation of the (CO)2 dimers has been observed when metastable states of the CO 2+ dications are populated.